2022
DOI: 10.3390/app122211344
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Zeolite Developed with 3-Aminopropyltriethoxysilane and Adsorption of Cu(II) from Aqueous Media

Abstract: In this work, we removed copper (II) from an aqueous solution by using zeolite modified with a silicon-organic monomer (3-aminopropyltriethoxysilane; APTES) depending on the pH, time, temperature, and initial concentration of Cu(II) ions. To confirm the modification process and assess the interaction between the modified zeolite and Cu(II), we performed instrumental analyses (XRD, SEM/EDX, TGA/DTA, BET, FT-IR, and XPS). We determined the maximum adsorption capacities of the modified zeolite for Cu(II) to be 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…When the Freundlich isotherm was used to fit the data, the correlation coefficients R 2 were 0.9976 for BBB and 0.9959 for N-BBB; while the n F values of BBB and N-BBB were 3.76 and 2.77. The results indicated that the adsorption processes were non-uniform multilayer [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the Freundlich isotherm was used to fit the data, the correlation coefficients R 2 were 0.9976 for BBB and 0.9959 for N-BBB; while the n F values of BBB and N-BBB were 3.76 and 2.77. The results indicated that the adsorption processes were non-uniform multilayer [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, natural zeolites received considerable attention due to their natural abundance, unique properties, low cost, non-toxicity, attractive physicochemical properties and efficiency in the adsorption of common pollutants [ 2 ] such as heavy metals, other inorganic compounds (ammonium, nitrites, nitrates, etc.) [ [3] , [4] , [5] , [6] , [7] , [8] , [9] ] and organic pollutants (pesticides, dyes, total petroleum hydrocarbons, etc.) [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%